The impact of inflation on U.S. productivity and international competitiveness / by Michael J. Boskin, Mark Gertler, and Charles Taylor - Boskin, Michael J.; Gertler, Mark; Taylor, Charles; NPA Committee on Changing International Realities (Washington, D.C : NPA Committee on Changing International Realities, 1980)
The authors conclude that much could be done by reforming the tax codes for private individuals and for corporations to reduce the detrimental effects of inflation.
Bibliography: p. 66-67.
osa; 8/08/18
Loans
Keywords: Competition, International; Industrial productivity; United States